The Inclusive Education for the Visually Impaired Students in Nepal: Integrating Systematic Reforms for Sustainable Development - Neupane, Arjun Bhakta (Academia Journal of Humanities & Social Sciences, 2026)
The inclusive education for the visually impaired students in Pokhara Metropolitan City, Nepal can be described as both successful and problematic. This study used a mixed-methods approach and incorporated the quantitative surveys of 50 respondents that included students, teachers, administrators, parents, community members, NGO representatives, and government officials. This methodological integration gave an all-inclusive knowledge the term ‘inclusive education’ from different perspectives. The results of the surveys demonstrated the moderate accessibility to the learning materials and supportive teaching practice, but the substantial barriers in the infrastructure and the use of assistive technologies and extracurricular activities. Key informant interviews affirmed that there are policies, which are not strongly implemented for teacher trainings.  Similarly, the resources are still scarce. The addition of focus group discussions provided an insight into the lived experiences of stigma, neglect, and slow progress and demanded a livelihood support in the families and more effective advocacy in the local area. Overall, the study showed that the inclusion of education in Pokhara Metropolitan City has to be a multi-layered undertaking. Effective inclusion is not limited to the policy frameworks, which relies on the practical investment in the available materials, infrastructure, and teacher capacity as well as community engagement to diminish stigma and facilitate a holistic involvement. Therefore, the inclusive education for the visually impaired students can shift towards a substantial and sustainable progress by integrating systemic reforms with the focus on the lived experiences.